Immunogenicity of COVID-19 vaccines and levels of SARS-CoV-2 neutralising antibody in the Bruneian population: Protocol for a national longitudinal study. Issue 12 (1st December 2022) - Ghani, Hazim; Ahmad, Liyana; Sharif, Hanisah; Wong, Justin; Bagol, Saifuddien; Alikhan, Mohammad Fathi; Taib, Surita; Tan, Chee Wah; Zhu, Feng; Ong, Xin Mei; Shim, Chin Yee; Wang, Yan; et al.
Abstract : Introduction: Neutralising antibodies (NAbs) have been shown to be correlative of immune protection against SARS-CoV-2. We report the protocol for a national longitudinal study to assess and compare the level of NAbs generated in response to COVID-19 vaccines in Brunei Darussalam in adults 2–6 weeks post primary series (BBIBP-CorV, AZD1222, or mRNA-1273 vaccines) and their subsequent follow-up after administration of a third (booster-1) dose (BBIBP-CorV, mRNA-1273, or BNT162b2). Methods and analysis: Participant data will be extracted and processed from the national electronic health record system (Bru-HIMS) and the national mobile health application (BruHealth) into a research data platform. Eligible adults who have received their primary or booster vaccine will be invited using a stratified random sampling strategy based on age, gender and vaccine type (baseline target population, n=3000; 2–6 weeks post last dose). Blood serum will be isolated, and NAb levels assessed using the cPass surrogate virus neutralisation test. Baseline participants will then be screened for eligibility for subsequent longitudinal analysis. Those who have received a third dose will be followed up at 1, 3, 6, 9 and up to 12 months. NAb levels will be evaluated across the participant population according to vaccine platform/booster type, time since the last dose and correlated with demographic data. The study period is from December 2021 to January 2023 and aims to evaluate how NAb levels wane following a third vaccine dose across different vaccine platforms and determine the impact and rate of breakthrough infections. Ethics and dissemination: This study has been approved by the Medical and Ethical Research Committee of Ministry of Health, Brunei Darussalam. Individual NAb test results will be shared with each participant by text message. The findings from this study will help policy-makers in Brunei develop future vaccination strategies and establish regulations across multiple agencies.